2022
DOI: 10.3390/nu14214553
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and Its Association with the Prevalence of Coronary Heart Disease among 45,306 US Adults

Abstract: Inflammation plays a pivotal in the occurrence and development of coronary heart disease (CHD). We aim to investigate the association between the Dietary Inflammatory Index (DII) and CHD in the present study. In this cross-sectional study, adult participants from the National Health and Nutrition Examination Survey (NHANES) (1999–2018) were enrolled. The social demographic information, lifestyle factors, blood biochemical measurements, dietary information, and CHD status of all the participants were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…PD is a chronic progressive neurological disorder characterized by the degeneration of dopaminergic neurons [17] . As is increasingly recognized, in ammation plays a crucial role in a wide range of pathological conditions and chronic diseases [18,19] . Numerous studies have investigated the relationship between PD and in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…PD is a chronic progressive neurological disorder characterized by the degeneration of dopaminergic neurons [17] . As is increasingly recognized, in ammation plays a crucial role in a wide range of pathological conditions and chronic diseases [18,19] . Numerous studies have investigated the relationship between PD and in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously published studies did, the DII that included 28 dietary components was calculated according to the protocol provided by Shivappa et al. ( 10 , 16 , 18 , 19 ). Briefly, six important systemic inflammation markers (IL-1β, IL-6, IL-4, IL-10, TNF-α, and CRP) were adopted to reflect the inflammation level.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: 1) age <18 or ≥80 years, 2) estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 , 3) pregnant individuals, 4) participants without dietary information. components was calculated according to the protocol provided by Shivappa et al (10,16,18,19). Briefly, six important systemic inflammation markers (IL-1b, IL-6, IL-4, IL-10, TNF-a, and CRP) were adopted to reflect the inflammation level.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the absolute value of DII, the stronger the effect of diet on inflammation. DII has been reported to strongly correlate with many chronic diseases, such as coronary heart disease [ 18 ], metabolic syndrome [ 19 ], cancer [ 20 ], and osteoarthritis [ 21 ]. Studies demonstrated that a low DII diet was related to improved BMD in postmenopausal women of different races [ 22–24 ].…”
Section: Introductionmentioning
confidence: 99%